Penerapan Etika Bisnis Islam Pada Rental Mobil Bilqis Wiyung Surabaya. - Claudya, Chika; Suryaningsih, sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2021)
This study aims to analyze the application of Islamic business ethics in car rental. The object of study is the bilqis car rental in Babatan Wiyung, Surabaya. Islamic business ethics refers to 5 axioms: monotheism, balance, free will, responsibility, and virtue. Research data collection was carried out by observation and interview methods. The analysis was carried out with a qualitative descriptive approach. The results show that the bilqis car rental is dishonest by the car rental owner who uses the car rental (motor) guarantee without the motorbike owner’s knowledge.